Visioning hope: embracing higher education's role with urban public charter schools - Bergeron, Bette S. (Urban Education, 2017)
The purpose of this study is to reflect on the evolution of a partnership between a university and urban charter high school serving a predominately African American population. Because of the author's embeddedness both as the researcher and participant member, this research assumes the paradigm of autoethnography. Reflections on key components of this evolution provide implications for teacher education, particularly in regard to a call for engagement between urban charter schools and educator preparation programs, and a challenge to higher education to analyze existing perceptions of public charter schools within a wider institutional mission to prepare educators for all children.
Keywords: African American students; charter school; dept.aa; high school; programs; teacher education; universities; urban education